Multi-omics reveals novel forage advantages of Potentilla anserina Linnaeus in high-salt habitats - Cui, Zhijia; Zhang, Xiaoling; Lv, Ziyang; Yang, Shangkun; Zhang, Miaomiao; Hou, Hanghang; Li, Jing; Yuan, Yuhao; Li, Junqiao; Feng, Baili (Frontiers in Microbiology, 2025)
IntroductionPotentilla anserina Linnaeus (P. anserina) is a traditional Chinese herbal medicine with ethnic characteristics that grows in the Qinghai-Tibetan Plateau. It has the potential to be used as a novel feed for ruminants. However, the large area of saline-alkaline soils makes it difficult to rationally use Portulaca oleracea as a feed.MethodsIn this study, the effects of volatile metabolites, non-volatile, bacteria and fungi in stems and leaves of P. anserina under three different treatments (fresh grass, hay and silage) in high-salt were investigated using metabolomics and microbiological methods.ResultsSilage under salt stress also improved crude protein and crude fat content compared to hay and fresh treatments. A total of 996 volatile and 928 non-volatile metabolites were identified. Among them, the main volatile substance of silage was 1-Nonen-3-one, while the non-volatile substance was 3-O-Methylgalangin. SC-I-84, Methyloversatilis, and Pseudomonas was specific to P. anserina forage, while Podosphaera is greatly reduced in high-salts. The Pseudomonas bacteria produced specifically improved the drought resistance and salt tolerance of P. anserina.DiscussionThese findings provide essential insights for valorizing P. anserina as a sustainable feed resource, supporting its potential application in animal production within saline-alkaline environments.